Implementasi Perma Nomor 7 Tahun 2022 Tentang E-Court Secara Prodeo Di Pengadilan Agama Rantauprapat Kelas I B - Hidayati, Nursitta; Lubis, Fauziah (Dinasti Review Publisher, 2024)
This research aims to examine in more depth how to implement PERMA Number 7 of 2022, especially regarding free E-courts in the Rantauprapat Class I B Religious Court. This research includes qualitative research using empirical juridical research methods that use two data sources, namely primary and secondary. Primary data sources consist of interviews with 6 (six) people who filed lawsuits, and 2 (two) clerks at the Rantauprapat Class I B Religious Court regarding the implementation of PERMA Number 7 of 2022, as well as secondary data originating from PERMA Number 7 of 2022, Supreme Court Circular Letter Number 10 of 2010, books and literature studies related to this research. The results of this research show that changes to PERMA Number 7 of 2022 cover several aspects, one of which is regarding online case registration using free. 5 (five) of the 6 (six) sources did not know about the existence of Supreme Court regulation Number 7 of 2022 and also E-court, and 4 (four) of the 6 (six) sources did not know about prodeo. In terms of implementing PERMA Number 7 of 2022 at the Rantauprapat Class I B Religious Court, we have tried our best to implement PERMA Number 7 of 2022, however, there are several inhibiting factors originating from internal, namely the lack of facilities and infrastructure as well as the pegawaif’s lack of knowledge regarding the implementation of e- court and also externally which consists of low public knowledge regarding technological sophistication, so that it cannot be implemented as a whole.